Husserl on Impersonal Propositions - Byrne, Thomas (Problemos, 2022)
The young Edmund Husserl stressed that the success of his philosophy hinged upon his ability to determine the subject and the predicate of impersonal propositions and their expressions, such as ‘It is raining’. This essay accordingly investigates the tenability of Husserl’s early thought, by executing the first study of his analysis of impersonal propositions from the late 1890s. This examination reshapes our understanding of the inception of phenomenology in two ways. First, Husserl pinpoints the subject by outlining why impersonal expressions are employed during communication. This contravenes interpretations of the early Husserl as uninterested in intersubjectivity. Second, by studying how Husserl determines the predicate by investigating existential propositions, I show that Husserl , in the late 1890s, came to his final view on the concept of being.
Keywords: Existential propositions; judgment; intersubjectivity; communication; impersonal propositions; descriptive psychology